'Disordered surroundings': money and socio-economic exclusion in Western Kenya. (11th April 2017) - Schmidt, Mario
Abstract: This article explores relations between ways of experiencing socio-economic disorder, strategies on how to deal with it, and monetary classifications that symbolize these ways and strategies. It assumes that we can learn something from the fact that the concept of pesa makech ('bitter money') has been replaced with the much more diffuse notion of pesa marach ('bad money') in Western Kenya during the last twenty-five years. This shift in how 'negative forms' of money are discursively marked indexes a change in the way in which the people of Kaleko, a small market centre in Western Kenya, conceptualize the disorder of their surroundings. Instead of interpreting disorder as an effect of events taking place inside their sphere of influence, residents of Kaleko now predominantly situate the cause of disorder in actions of external actors that are perceived as uncontrollable: the 'economy', money itself, politicians, members of other ethnic groups and untrustworthy Luo. This necessarily changes the ways in which disorder is tackled: while pesa makech 's bitterness could be resolved by 'sorting out' ( rieyo ) the homestead's disorder, nowadays people employ other ways that aim at resolving disorder: upscaling rieyo 's potential to the Kenyan nation; 'struggling' ( chandre ) through disorder; and relativizing rieyo 's applicability. Résumé: Cet article explore les liens entre les modes d'expérience du désordre socioéconomique, les stratégies pour y faire face, et les classifications monétaires qui symbolisent ces modes et stratégies. Il suppose que l'on peut apprendre quelque chose du fait que le concept de pesa makech (« argent amère ») a été remplacé par la notion bien plus diffuse de pesa marach (« mauvais argent ») dans l'Ouest du Kenya au cours des vingt-cinq dernières années. Ce changement dans la manière d'utiliser des « formes négatives » d'argent comme marqueurs discursifs indique un changement dans la manière dont les habitants de Kaleko, une petite ville de marché de l'Ouest du Kenya, conceptualisent le désordre de leur environnement. Au lieu d'interpréter le désordre comme l'effet d'événements survenant au sein de leur sphère d'influence, les résidents de Kaleko situent aujourd'hui principalement la cause du désordre dans l'action de facteurs extérieurs perçus comme incontrôlables : l'« économie », l'argent lui-même, les politiciens, les membres d'autres groupes ethniques et les Luo, peu dignes de confiance. Ceci change nécessairement la façon de faire face au désordre : là où il était possible de résoudre l'amertume du pesa makech en « rangeant » ( rieyo ) le désordre du foyer, on emploie aujourd'hui autres moyens de résoudre le désordre : appliquer le potentiel du rieyo à l'échelle de la nation kenyane ; « se débattre » ( chandre ) à travers le désordre ; et relativiser l'applicabilité du rieyo.